حجاجية المجاز المرسل في مقامات بديع الزمان الهمذاني - عِمران, علي (جامعة الوادي - University of Eloued, 2021)
حجاجية المجاز المرسل في مقامات بديع الزمان الهمذاني د. علي أحمد عمران أستاذ البلاغة والأدب والنقد المشارك الجامعة الأهلية- مملكة البحرين dr.aliomran7@gmail.com Tel:0097339996691 الملخص يعدُّ المجاز من الأساليب المهمّة في توصيل المعاني والأفكار، فهو يخاطب في الأعم الأغلب الوجدان بهدف تحقيق أقصى إمكانات التأثير والاستمالة والإقناع. وقد برز المجاز المرسل بشكلٍ كبيرٍ في خطابات بديع الزمان الهمداني( 395ه) الذي يعدُّ خطابًا إقناعيًا بامتياز. وعلى هذا الأساس رُمنا البحث في هذا المُعطى من خلال مقال وسمناه ب" حجاجية المجاز المرسل في مقامات بديع الزمان الهمذاني"، وتناولنا بعد التمهيد مفهوم المجاز وعلاقاته، ثمّ عرَّفنا الحجاج وتقنياته وحدّدنا علاقات المجاز المرسل بالحجاج، وصولًا إلى توظيف هذه المكتسبات النظريّة في نظير لها تطبيقيٍّ تمثّل بعض نماذج من المجاز المرسل في مقامات الهمذاني.. وعليه، سنحاول في هذا البحث استثمار المعرفة الحجاجية في مقاربة نصوص الهمذاني في مقاماته المختلفة، لكشف القوانين التي تحكمها علاقات المجاورة في المجاز المرسل، بوصفها مداخل حجاجية يوظفها المخاطِب من أجل توريط المخاطَب في رهانات الخطاب المرصودة. ونهدف من خلال هذه الخطاطة إلى إماطة اللّثام عن بعض الجوانب الخاصّة بهذا الموضوع الجدير بالدِّراسة والتحليل والاستنتاج. الكلمات المفتاحيّة: الحجاج، المجاز المرسل، المعاني، الأسلوب، الخطاب. The argumentation of metonymy in Badi al-Zaman al-Hamdhani’s Maqamat (musical structures) Abstract Metonymy is one of the important methods of communicating meanings and ideas. as it addresses in the most general sense the human conscience with the aim of achieving the maximum potential of influence, allurement and persuasion. Metonymy has emerged greatly in the speeches of al-Hamdani (395 AH), which is considered a persuasive speech par excellence. On this basis this research aims to address this fact through the article ‘The argumentation of metonymy in Badi al-Zaman al-Hamdhani’s Maqamat (musical structures). After the introduction, it deals with the concept of metonymy and its relationships. Then the study introduces the concept of argumentation and its techniques, and the relationship of argumentation and metonymy, leading to the use of these theoretical gains in an analogous way. In practice, it is represented through some examples of metaphors that are transmitted in the Maqamat of al-Hamdhani. Accordingly, this research attempts to invest in the argumentative knowledge in the approach of the texts of al-Hamdani in his various Maqamat, to reveal the laws (cause, transformation, extent, solutions) that are governed by neighboring relations in metonymy, as an argumentative entry point that the addressee uses in order to implicate the respondent in bets monitored speech. The research aims, through this plan, to uncover some aspects of this topic that are worthy of study, analysis and conclusion. Keywords: Argument, Metonymy, Meanings, Style, Speech.
مقال
Keywords: الحجاج، المجاز المرسل، المعاني، الأسلوب، الخطاب; Argument, Metonymy, Meanings, Style, Speech